2021
DOI: 10.1186/s13195-021-00873-w
|View full text |Cite
|
Sign up to set email alerts
|

Plasma amyloid-β oligomerization assay as a pre-screening test for amyloid status

Abstract: Objective We assessed the performance of plasma amyloid oligomerization tendency (OAβ) as a marker for abnormal amyloid status. Additionally, we examined long-term storage effects on plasma OAβ. Methods We included 399 subjects regardless of clinical diagnosis from the Amsterdam Dementia Cohort and European Medical Information Framework for AD project (age, 63.8 ± 6.6; 44% female). Amyloid status was determined by visual read on positron emission t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 43 publications
0
15
2
1
Order By: Relevance
“…Other than the ultrasensitive technique of the conventional ELISA that uses epitope-overlapping Aβ antibodies to capture and detect Aβ multimers after spiking the plasma samples, using synthetic Aβ42 to enhance the oligomerization of Aβ 27 28 29 was recently approved by the Korean National Evidence-based Healthcare Collaborating Agency as a supplementary diagnostic tool for AD (#HTA-2021-81, https://nhta.neca.re.kr/nhta/publication/nhtaU0601L.ecg ).…”
Section: New Technologies For Measuring Blood Biomarkersmentioning
confidence: 99%
See 1 more Smart Citation
“…Other than the ultrasensitive technique of the conventional ELISA that uses epitope-overlapping Aβ antibodies to capture and detect Aβ multimers after spiking the plasma samples, using synthetic Aβ42 to enhance the oligomerization of Aβ 27 28 29 was recently approved by the Korean National Evidence-based Healthcare Collaborating Agency as a supplementary diagnostic tool for AD (#HTA-2021-81, https://nhta.neca.re.kr/nhta/publication/nhtaU0601L.ecg ).…”
Section: New Technologies For Measuring Blood Biomarkersmentioning
confidence: 99%
“… 44 An association of increased Aβ level with an AD diagnosis and amyloid PET positivity was also found when using an ELISA-based multimer detection system (MDS) that measures oligomerized Aβ. 27 28 29 This MDS utilizes the aggregation tendency of blood Aβ to measure multimeric Aβ levels. The distinctive assay principle of MDS is thought to produce the opposite result.…”
Section: Aβ Biomarkersmentioning
confidence: 99%
“…Specific antibodies are used in MDS, and the level of OAβ can be obtained by using a spectrophotometer. As the OAβ test has the potential for distinguishing between AD patients and healthy controls, MDS would be a promising method for AD diagnosis, for example, AlphalLISA assay and the Blood TM OAβ test (PeopleBio Inc., South Korea) (Lee et al, 2020;Babapour Mofrad et al, 2021;Dominguez et al, 2022).…”
Section: Multimer Detection System-oligomerized Amyloid Beta (Mds-oaβ)mentioning
confidence: 99%
“…Amyloid PET has been used as a standard biomarker for participant selection in many clinical trials. Mofrad et al demonstrated a sensitivity of 76% and specificity of 67% for predicting amyloid PET positivity by using plasma MDS-OAβ and this technique reduced the costs and number of PET scans needed to screen for amyloidosis [13]. In this study, we tested various machine learning models to predict amyloid PET positivity using In clinical AD prediction, MDS-OAβ has been validated and commercialized using heparinized plasma, and previous studies have used these samples [10].…”
Section: Introductionmentioning
confidence: 99%